Meningkatkan Hasil Belajar Bahasa Inggris Pada Materi Introducing One Self Dengan Menggunakan Model Pembelajaran Think Pair Share Di Kelas V SD Negeri 33 Buton - Nur Dahniar; Niluh Aditia Wati; Waode Nining Dwi Fahmi (Journal on Education, 2024)
This research aims to improve student learning outcomes by using the Think Pair Share learning model for students at SD Negeri 33 Buton. By using the PTK method, the research results show that there is a significant increase in student learning outcomes using the Think Pair Share learning model. These results have important implications in developing learning models in the context of language education, showing that this learning model has contributed to improving the learning outcomes of class V students at SD Negeri 33 Buton regarding the material Introducing One Self. These findings provide valuable guidance for the development of more effective and engaging learning models in the current educational era.